Agonistic anti-CD40 antibodies in patients with solid tumors: a systematic review and evidence map of clinical safety, with exploratory proportional synthesis - Xinrui Yin; Shijia Du (Frontiers in Immunology, 2026)
Background Agonistic anti-CD40 antibodies and related CD40 agonist biologics are being developed across multiple solid tumors using diverse biologic formats, delivery routes, and combination regimens. Safety is central to their clinical development but remains difficult to interpret because high-grade adverse events in combination settings may reflect partner therapies, and safety outcomes are reported inconsistently. Methods We conducted a systematic review and evidence map of the clinical safety of CD40 agonists in patients with solid tumors. Major bibliographic databases, trial registries, and conference sources were searched. Reports from the same trial population were linked to avoid double counting. Safety-reporting availability was prespecified as a primary output, and exploratory proportional synthesis was performed only when patient-level event counts and denominators were clearly reported or could be reproducibly derived. Clinical activity and immunological or pharmacodynamic findings were summarized descriptively. Results Twenty-seven independent peer-reviewed primary safety reports covering 12 agents or biologics were included. The evidence base was uneven and concentrated in conventional systemically administered monoclonal antibodies, basket or mixed-tumor populations, pancreatic cancer, and melanoma. Fc-engineered, tumor-targeted or bispecific, non-monoclonal-antibody, and intratumoral or locally delivered approaches were each represented by few reports, precluding comparison by format or route. Patient-level safety counts and denominators were inconsistently reported, and cytokine-release grading frameworks varied or were unspecified. Several clinically important outcomes were therefore suitable for mapping but not pooling. Four exploratory pools were interpreted as hypothesis-generating: any-grade treatment-related adverse events were consistently frequent but had limited value for distinguishing clinically important toxicity, whereas high-grade and treatment-related estimates were imprecise. In combination studies, pooled estimates reflected regimen-level toxicity rather than toxicity attributable specifically to CD40 agonism. Clinical activity and immunological or pharmacodynamic findings were widely reported but too heterogeneous for formal comparison. Conclusion This review provides a structured map of where CD40 agonist safety evidence is available and where important gaps remain. Current evidence does not support definitive comparison of toxicity across biologic formats, delivery routes, or treatment regimens. More consistent patient-level reporting, with explicit denominators, treatment attribution, and grading frameworks, is needed to enable future comparative safety assessment. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/ , identifier CRD420261414658.